Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, M.; Hausotte, T. (Key Engineering Materials)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Über die Abgrenzung von Auflösungskonzepten in der industriellen Computertomografie - Binder, Felix; Hausotte, Tino (tm - Technisches Messen)
Unter dem Begriff der Auflösung wird für gewöhnlich das kleinste messbare Merkmal eines Messsystems verstanden. In der dimensionellen Computertomografie hingegen haben sich in den vergangenen Jahren mehrere Auflösungskonzepte etabliert, die aufgrund der fehlenden Normung zueinander im Kontrast stehen. In diesem Beitrag werden die drei häufigsten Konzepte, die Voxelgröße, die Ortsauflösung und die metrologische Strukturauflösung in Kürze vorgestellt. Anschließend wird eine Abgrenzung zwischen den Konzepten getroffen und ein Integration der bestehenden Konzepte in ein gemeinsames Amplituden-Wellenlängen Diagramm diskutiert.
Keywords: Electrical and Electronic Engineering; Instrumentation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Die Erkennbarkeit von Rissen und geometrischen Qualitätskennwerten von Fügeverbindungen mittels Computertomografie ist von der Interfacestrukturauflösung abhängig, welche mittels geeigneter Prüfkörper untersucht wird. Die Reduktion von Abbildungsartefakten im Bereich von Bauteilzwischenräumen und -oberflächen verbessert deren dimensionelle Erfassbarkeit.
Keywords: Electrical and Electronic Engineering; Instrumentation

Application of an edge detection algorithm for surface determination in industrial X-ray computed tomography - Busch, M.; Hausotte, T. (Production Engineering)
Surface determination is an essential step of the measurement process in industrial X-ray computed tomography (XCT). The starting point of the surface determination process step is a single grey value threshold within a voxel volume in conventional surface determination methods. However, this value is not always found in the reconstructed volume in the local environment of the surface of the measurement object due to various artefacts, so that none or incorrect surfaces are determined. In order to find surfaces independently of a single grey value, a three-dimensional approach of the initial contour determination based on a Prewitt edge detection algorithm is presented in this work. This method is applied to different test specimens and specimen compositions which, due to their material or material constellation, their geometric properties with regard to surfaces and interfaces as well as their calibrated size and length dimensions, embody relevant properties in the examination of joining connections. It is shown that by using the surface determination method in the measurement process, both a higher metrological structure resolution and interface structure resolution can be achieved. Surface artefacts can be reduced by the application and it is also an approach to improved surface finding for the multi-material components that are challenging for XCT.

Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuation.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Materials Science (miscellaneous)

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (e-Journal of Nondestructive Testing)
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-estructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.